Damping performance of the degraded fluid viscous damper due to oil leakage. (February 2023) - Hu, Shangtao; Yang, Menggang; Meng, Dongliang; Hu, Renkang
Abstract: As a typical passive energy dissipation device, fluid viscous dampers (FVDs) are widely employed to alleviate seismic-induced structural vibration. However, oil leakage often occurs in FVDs, which has been identified as a critical factor that may cause deterioration in their mechanical behaviors. This study aims to evaluate the damping performance of the leaked FVD. To obtain the mechanical properties, a series of cyclic tests were conducted on a large-tonnage FVD with different oil leakage levels. The performance degradation mechanism was revealed through the finite element method, and analytical models for simulating the hysteresis characteristics of the leaked FVD were established and verified. A long-span cable-stayed bridge subjected to harmonic excitations was used as a case study to show the impact of leakage and load intensity on the bridge responses and the damper performance. The results reveal that oil leakage will cause a "gap" phenomenon in the hysteresis curves (i.e., the damper does not generate damping force), but it will not alter the mechanical parameters of the FVD following the gap has been consumed. The reason for this phenomenon is that air would flow through the orifices prior to silicone oil when being compressed. A negative correlation is found between the vibration mitigation effectiveness of FVD and the leakage level. However, the degree of performance degradation will be minimized when subjected to higher-intensity excitations. A leaked FVD is more prone to force-exceeding and stroke-exceeding failures thus it should be replaced soon.